Characteristics of the early miocene globigerinid-rich siliciclastic-carbonate reservoirs in ultra-deep water areas of the Baiyun sag, pearl river mouth basin, South China sea - Ma, Yongkun; Xu, Leyi; Jiang, Han; Yao, Siyi; Wang, Xiaomeng; Sun, Hui; Chen, Beichen (Frontiers in Earth Science, 2026)
Exploring new types of high-quality reservoirs in terrigenous clastic-starved (ultra-)deep-water areas is a crucial component in ensuring future energy supply. Recent drilling (water depth >1,500 m) in the Pearl River Mouth Basin revealed globigerinid-rich mixed siliciclastic-carbonate rocks with high porosity and low permeability physical properties, providing promising exploration opportunities. Based on core, logging and seismic data across critical wells in ultra-deep water areas (>1,500 m deep) aside the Yunli Low Uplift, this study presents the reservoir properties of the Early Miocene globigerinid-rich siliciclastic-carbonate rocks. These rocks contain 10%–80% terrigenous components and 5%–45% biogenic carbonate grains dominated by Globigerina shells (>90%). Shell chambers exhibit as those are hollow and those filled with carbonates (e.g., micrite, sparite, dolomite) or quartz, glauconite, analcime, and pyrite. Well-preserved visceral foramen pores contribute to reservoir spaces, exhibiting with high porosity (up to 37.7%, average 17.43%). However, interstitial micrite and clay, along with authigenic ferroan calcite and ferroan dolomite, severely reduce permeability (average 0.148 × 10-3μm2). Accompanied with the Globigerina enrichment within seabed sediments, appropriate amounts of terrigenous components/moderate bottom current dynamics help constrain the chamber fillings from carbonate cementation/micrite and clay matrix. These findings provide theoretical insights for exploring new types of deep-sea high-quality reservoirs.